The Kunene anorthosite complex, Namibia, and its satellite intrusions: Geochemistry, geochronology, and economic potential - Maier, W.; Rasmussen, Birger; Fletcher, I.; Barnes, S.; Huhma, H. (Society of Economic Geologists Inc, 2013)
The Kunene Complex of Namibia-Angola is one of the largest anorthosite massifs on Earth (up to 18,000 km2), consisting of several distinct anorthosite and leucotroctolite intrusions. The Namibian portion of the Kunene Complex measures ~80 × 50 km, ~4,000 km2, and is dominated by the Zebra Mountain lobe, a ~16-km-thick dome-like mass of interlayered, relatively unaltered dark leucotroctolite with relatively altered, “white,” anorthosite. Past studies and the present work have found evidence for intrusion of two distinct phases of dark leucotroctolite into the white anorthosite, namely a relatively early, deformed, phase dated at 1363 ± 17 Ma (U-Pb in baddelyite), and a relatively later and undeformed phase whose absolute age remains unknown. The Kunene leucotroctolites are among the least evolved troctolites known from anorthosite complexes, with olivine containing 59 to 77 mol % forsterite and up to 1,700 ppm Ni, and plagioclase containing 56 to 69 mol % anorthosite. Our isotope data from the troctolites indicate a relatively small crustal component (δ18O, ~5.3–7.3; δ34S, 0.5–1; and ɛNdT, 0.9–1.8), whereas Nd and oxygen isotope data from the white anorthosites, published by other workers, showed a slightly larger crustal component (e.g., ɛNdT as low as −3; δ18O up to 7.5‰).In the periphery of the Kunene Complex are several, relatively small (<10 km2), mafic-ultramafic intrusions comprising peridotite, pyroxenite, gabbro, troctolite, and anorthosite. Some of these bodies are Ni-Cu-PGE mineralized, including the Ohamaremba troctolite, the Oncocua pyroxenite, and the Ombuku peridotite-gabbronorite. The latter additionally contains a massive chromitite layer. A new U-Pb baddelyite age of 1220 ± 15 Ma for Ohamaremba indicates that the latter postdates the main Kunene Complex by ~140 Ma. The relative enrichment in MgO, Cr, and Ni, and the O, Nd, and S isotope characteristics of Kunene magmatism suggest that the primary magmas were predominantly mantle-derived picrites or basalts. The massif-type anorthosites formed through ascent of feldspathic slurries followed by downward draining of residual liquid. Subsequent magma pulses formed troctolitic sills within the anorthosite plutons and mafic-ultramafic satellite intrusions in the periphery of the anorthosites. The recurring nature of Kunene mafic-ultramafic magmatism results from several successive mantle upwellings. Partial mantle melts ascended through reactivated translithospheric lineaments along the southern margin of the Congo craton.